The gut-lung axis in severe pneumonia-related lung injury: mechanisms and therapeutic strategies - Sun, Qiongling; Gao, Jun; Zhao, Xuan; Wang, Tianyi; Pan, Wensen; Yu, Jing (Frontiers in Immunology, 2026)
Severe pneumonia-related lung injury is a life-threatening condition associated with high morbidity and mortality. Recent advances in research on the gut-lung axis have provided novel insights into its pathophysiology and revealed potential therapeutic targets. Within the conceptual framework of the microorganism-immunity-metabolism network, modulation of the gut microbiota has emerged as a promising strategy for intervention. Therapeutic approaches such as probiotics, prebiotics, synbiotics, and fecal microbiota transplantation aim to enhance microbial diversity and alter metabolite profiles, thereby optimizing immune responses and attenuating systemic and pulmonary inflammation. This review explores the mechanistic underpinnings of the gut-lung axis in the context of severe pneumonia-related lung injury, with a particular focus on microbiota-targeted interventions. Our goal is to provide a theoretical foundation for the clinical application of gut microbiota modulation in the prevention and treatment of severe pneumonia-related lung injury.